2007
DOI: 10.1007/s00248-006-9164-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Endophytic Bacteria from the Nickel Hyperaccumulator Plant Alyssum bertolonii

Abstract: We report the isolation and characterization of endophytic bacteria, endemic to serpentine outcrops of Central Italy, from a nickel hyperaccumulator plant, Alyssum bertolonii Desv. (Brassicaceae). Eighty-three endophytic bacteria were isolated from roots, stems, and leaves of A. bertolonii and classified by restriction analysis of 16S rDNA (ARDRA) and partial 16S rDNA sequencing in 23 different taxonomic groups. All isolates were then screened for siderophore production and for resistance to heavy metals. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(92 citation statements)
references
References 45 publications
4
78
1
5
Order By: Relevance
“…Moreover, in Thlaspi (Idris et al 2004), more isolates tolerant to higher Ni concentration were found in the plant endosphere than in the rhizosphere, thus reinforcing the hypothesis that Ni-hyperaccumulating plants provide highly selective and peculiar niches for bacteria. In agreement with this finding, endospheres from roots, shoots and leaves of A. bertolonii were shown to contain bacterial isolates possessing different levels of Niresistance (Barzanti et al 2007) although the biological reasons for such differences is elusive yet. Notably, isolates from leaves displayed the lowest levels of Niresistance compared with those from the other organs in agreement with a low Ni bioavailability due to vacuolar storage of Ni in epidermal cells and trichomes (Ingle et al 2008;Kupper et al 2001;Smart et al 2007).…”
Section: Bacterial Communities In Serpentine Soilmentioning
confidence: 53%
“…Moreover, in Thlaspi (Idris et al 2004), more isolates tolerant to higher Ni concentration were found in the plant endosphere than in the rhizosphere, thus reinforcing the hypothesis that Ni-hyperaccumulating plants provide highly selective and peculiar niches for bacteria. In agreement with this finding, endospheres from roots, shoots and leaves of A. bertolonii were shown to contain bacterial isolates possessing different levels of Niresistance (Barzanti et al 2007) although the biological reasons for such differences is elusive yet. Notably, isolates from leaves displayed the lowest levels of Niresistance compared with those from the other organs in agreement with a low Ni bioavailability due to vacuolar storage of Ni in epidermal cells and trichomes (Ingle et al 2008;Kupper et al 2001;Smart et al 2007).…”
Section: Bacterial Communities In Serpentine Soilmentioning
confidence: 53%
“…At present, however, little evidence is available concerning the effect of metal hyperaccumulation and metal-based defences upon the endophytic bacteria of hyperaccumulator plants. Two studies have surveyed the endophytes associated with nickel hyperaccumulator plants on natural serpentine soils [19,20]. Both reported that these bacteria showed high nickel tolerance, supporting the notion that the plants provide a high-metal environment for bacteria.…”
Section: Introductionmentioning
confidence: 90%
“…Plant samples (leaves, stems, roots, flowers, fruits) were washed thoroughly with tap water followed by sterile double distilled water and drained before immersion in 70% ethyl alcohol for 30s and sodium hypochlorite solution (2%) for 2min. The plant parts were then immersed in 70% ethyl alcohol for 30s (Barzanti et al 2007) and then rinsed with sterile double distilled water. Each plant part was cut aseptically into 1cm long segments using a sterile blade under the laminar flow hood and allowed to dry.…”
Section: Plant Sample Collectionmentioning
confidence: 99%